1995
DOI: 10.1007/bf01954268
|View full text |Cite
|
Sign up to set email alerts
|

Testicular degeneration in three patients with the persistent müllerian duct syndrome

Abstract: The high incidence of degeneration of testicular tissue in the persistent müllerian duct syndrome could be indirectly linked to anatomical abnormalities which could favour testicular torsion, known to induce testicular regression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 28 publications
0
28
0
3
Order By: Relevance
“…In the 3 cases described by Imbeaud et al [1995], testicular regression was present already at an early age (birth, 3 and 6 years, respectively). In our 3 patients of family 1, both testes failed to descend, suggesting a severe developmental defect.…”
Section: Discussionmentioning
confidence: 99%
“…In the 3 cases described by Imbeaud et al [1995], testicular regression was present already at an early age (birth, 3 and 6 years, respectively). In our 3 patients of family 1, both testes failed to descend, suggesting a severe developmental defect.…”
Section: Discussionmentioning
confidence: 99%
“…In 2 of our cases, transverse testicular ectopia was the only sign of an AMH mutation, as müllerian derivatives had regressed normally. Rarely, one or both testes are missing in patients fulfilling the criteria for PMDS [Imbeaud et al, 1995a;Souto et al, 1995;El-Gohary, 2003]. Testicular torsion, facilitated by the abnormal mobility of the testes, has been incriminated [Chaabane et al, 2010].…”
Section: Position Of the Testesmentioning
confidence: 99%
“…Endocrine investigations in PMDS usually show that Leydig cell function is normal, except in patients with testicular degeneration [Imbeaud et al, 1995a]. The AMH concentration in serum depends upon the molecular origin of the disorder.…”
Section: Endocrine Investigationsmentioning
confidence: 99%
“…Fertility is rare in patients with PMDS. Imbeaud et al reported three cases of PMDS with testicular degeneration and opined that anatomical abnormality may favour testicular torsion and early loss of testis [11].…”
Section: Discussionmentioning
confidence: 99%